Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

So far I have $$\lim_{a \rightarrow -N} J_{a} = \lim_{a \rightarrow -N} \mid \frac{x}{2} \mid^a \sum_{k=0}^{\infty} \frac{(-x^2/4)^k}{k! \; \Gamma(a+k+1)} = \mid \frac{x}{2} \mid^{-N} \sum_{k=0}^{\infty} \frac{(-x^2/4)^k}{k! \; \Gamma(-N+k+1)}$$ I don't see how the $(-1)^n $ gets factored out to get the desired result of $(-1)^n J_{-N}$. Where $J_{a}$ is the Bessel function of the first kind. I am an undergrad student learning Bessel and Legendre ODE's. I know only basic cal and have a reference sheet of gamma and beta function properties. I don't have graduate school background on their meaning etc. so explaining to that detail really won't help me because of my background. I am looking more for math manipulation at this point. Thanks.

share|cite|improve this question
The reflection formula for the Gamma function might help. – marty cohen Oct 7 '12 at 21:28
up vote 2 down vote accepted

Use the fact that the reciprocal of the Euler's $\Gamma$-function vanishes at non-positive integers, that is for $k\in \mathbb{Z}_{\leqslant 0}$ $$ \lim_{x \to -k} \frac{1}{\Gamma(x)} = 0 $$ Thus, all the terms where $ 0 \leqslant k < N$ vanish in the limit: $$\begin{eqnarray} \lim_{a \to -N} J_a(x) &=& \sum_{k=N}^\infty \left(\frac{x}{2}\right)^{2k-N} \frac{(-1)^k }{k! \cdot \Gamma(1-N +k)} = \sum_{k=0}^\infty \left(\frac{x}{2}\right)^{2k+N} \frac{(-1)^{k+N}}{\Gamma(k+N+1) \cdot k!} \\ &=& (-1)^N J_N(x) \end{eqnarray} $$

share|cite|improve this answer
I don't understand how you get the last step in your final result. How does -N become +N ? I initially though you added k+N whenever there was k, but then I noticed that didn't work. Thanks! – renagade629 Oct 7 '12 at 22:27
I made a shift of the summation variable $k=N+m$. Then $k! = \Gamma(k+1) = \Gamma(m+N+1)$, $\Gamma(1-N+k) = \Gamma(1+m) = m!$ and $2k-N = 2(m+N) -N = 2m + N$. Now relabel $m$ as $k$. – user40314 Oct 9 '12 at 21:55

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.